Evaluation of the Implementation of ISO 9001:2015 Quality Management System on HR Performance - Nawwar, Maritza; Safirin, Mochamad Tutuk (Newinera Publisher, 2025)
This research was conducted to measure the extent to which the implementation of the ISO 9001:2015 Quality Management System influences the HR performance of PT XYZ using the ISO 9001:2015 clause, namely Organizational Context, Leadership, Operations, Performance Evaluation, and Improvement as measuring tools. This research is quantitative in nature and the data was distributed to 56 PT XYZ staff using Google Form. The data obtained will be processed using SPSS software with the multiple linear regression analysis method. From the results obtained, it is known that the regression analysis equation is Y = 0.428 + 0.040X1 + 0.099X2 – 0.110X3 + 0.078X4 + 0.122X5. It can be said that the variables Leadership (X2), Performance Evaluation (X4), and Improvement (X5) have a significant influence on HR performance. This is supported by the linear regression equation which obtained a positive value on HR performance. Apart from that, with the linearity test it can be seen that the data produced is linear in relation to HR performance because the results obtained are greater than 0.05. Therefore, this research can be a consideration for improving the ISO 9001:2015 Quality Management System on HR performance.